A Rare Parathyroid Carcinoma in Young Adult Man: Therapeutic Challenges in Tertiary Hospital with its Limitations - Sitanggang, Rupita Sari Endangena; Azhar, Yohana; Agustina, Hasrayati (Indonesian Journal of Cancer, 2024)
Introduction: Parathyroid carcinoma is a rare malignant neoplasm. The symptoms that arise are related to hyperparathyroid conditions, which are clinically difficult to distinguish between benign and malignant disorders. These conditions make the diagnosis and treatment of parathyroid carcinoma challenging. Case Presentation: : In this case report, a 27-year-old male presented with weak limbs and a history of multiple recurrent fractures. Serum calcium ions and parathyroid hormone levels were increased. A comprehensive history taking, laboratory testing, and radiographic examination were used to confirm the diagnosis of parathyroid cancer. However, a histological study is still necessary to make a certain diagnosis. The patient underwent parathyroidectomy accompanied by intraoperative frozen section examination, then confirmed to have parathyroid carcinoma. Calcium serum evaluations were performed on the patient after surgery. Conclusions: Parathyroid carcinoma is a very rare case. Clinical manifestations and the results of investigations that are not typical and rarely found together in one patient’s condition make the diagnosis of this case very difficult. Although recommendations or standard protocols in the management of parathyroid carcinoma do not yet exist, the results of case reports are expected to increase the knowledge and management of parathyroid carcinoma patients.